A new species of Zoniopoda Stål (Orthoptera: Acridoidea: Romaleidae) from Argentina and its phylogenetic position within the genus - Pocco, Martina Eugenia (2011)
A new species of the romaleid grasshopper genus Zoniopoda Stål (Romaleidae: Romaleini) is described and illustrated from the Sierras Chicas of Córdoba Province, central Argentina. A cladistic analysis based on morphological characters indicates that the genus Zoniopoda constitutes a monophyletic group and that Zoniopoda serrana n. sp. must be assigned to Iheringi species group based on synapomorphies of the pronotum and body color. The new species is similar to Z. similis Bruner from Paraguay, Bolivia and Brazil, from which it can be distinguished by the color pattern of the body, shape of the pronotal dorso-median carina and characters of the male terminalia and epiphallus. This paper has been formatted with embedded links to images of the type specimen, maps based on georeferenced specimen data for the genus and an updated key to the species of Zoniopoda available on the Orthoptera Species File (OSF) online (http://orthoptera.speciesfile.org).